A method for preparing a two-dimensional heterojunction material
By loading metal or metal oxides on the surface of titanium dioxide nanosheets and oxidizing treatment, homogeneous heterojunctions were prepared, which solved the problems of low surface area and few reaction sites on the existing surface heterojunctions, significantly improving the photocatalytic efficiency .
Patent Information
- Application Number
- CN202310087091.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-01-30
AI Technical Summary
The specific surface area of existing surface heterojunctions is low and the catalyst reaction sites are few, resulting in low photocatalytic efficiency.
Titanium dioxide nanosheets were prepared by hydrothermal method, and the metal or metal oxides were loaded on their surface, followed by oxidation by oxidizing agent, and finally the loaded product was removed to prepare homogeneous heterojunction [101]-[oxidation 101] materials.
The homogeneous heterojunction was successfully constructed, which greatly promoted the separation of electron holes, improved the photocatalytic efficiency, and was stable in structure, providing a rich reaction site.
Smart Images

Figure CN115920872B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalyst heterojunction, and in particular relates to a method for preparing a two-dimensional same-plane heterojunction material. Background Art
[0002] With the rapid growth of the world's population and the rapid development of industry, mankind is facing an unprecedented environmental and energy crisis. In order to ensure the sustainable development of human society, it is urgent to develop a green technology to achieve the green preparation of clean energy and the green management of the environment. Among the many advocated technologies, photocatalytic technology has great potential because it can directly use cheap and abundant sunlight to achieve the production of chemical fuels (such as hydrogen, methanol) and the degradation of harmful pollutants. Efficient photocatalysts need to have the following characteristics: ⅰ High efficiency of photogenerated carrier separation; ⅱ Strong redox potential. The emergence of nanostructure / nanolayer-photocatalysts has opened up a feasible path for the preparation of photocatalysts with specific physicochemical, structural, and optical properties.
[0003] Non-metallic doping, metal doping, and heterojunction construction are effective strategies to effectively inhibit the recombination of photogenerated electrons and holes in semiconductors. Among these strategies, the construction of heterojunctions is the most advocated because of its feasibility and high efficiency in separating electrons and holes. Five different heterojunctions include: traditional type-Ⅱ heterojunction, pn heterojunction, surface heterojunction, direct Z-type heterojunction, and semiconductor graphene heterojunction. Traditional type-Ⅱ heterojunction materials play a very important role in promoting the separation of electrons and holes, but as the electrons and holes move in a directional manner, their oxidation and reduction abilities will be weakened. In contrast, direct Z-type heterojunctions can produce holes and electrons with higher redox potentials, but the electrons on semiconductor I combine with the holes on semiconductor II, resulting in the recombination of photogenerated carriers, which consumes a portion of the photogenerated electrons and holes to a certain extent, thereby reducing the overall photocatalytic efficiency. In addition, traditional type-Ⅱ heterojunctions, pn heterojunctions, and semiconductor graphene heterojunctions are often achieved by combining two materials through a specific surface. However, due to external interference factors such as temperature differences, it is easy to cause the two materials to separate and fall off, resulting in the destruction of the heterojunction structure, which in turn leads to a decrease in photocatalytic efficiency. Surface heterojunctions are effective in promoting electron-hole separation. They are achieved through different crystal planes of a single semiconductor. Although the problem of material shedding is avoided, the contact sites between reactants and catalysts are reduced due to their block structure and low specific surface area. Therefore, it is very necessary to develop a method for preparing heterojunctions that can effectively promote the effective separation of electrons and holes, have a stable structure, and provide abundant reaction sites to comprehensively improve photocatalytic efficiency. Summary of the invention
[0004] The present invention aims to solve the problems of low specific surface area and few catalyst reaction sites of existing surface heterojunctions, and proposes a method for preparing a two-dimensional same-plane heterojunction material. The present invention can effectively promote the separation of electrons and holes, has a stable structure, and provides abundant reaction sites, thereby comprehensively improving the photocatalytic efficiency.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a two-dimensional same-plane heterojunction material, first using a hydrothermal method to prepare titanium dioxide nanosheets, then loading a protective metal or metal oxide on its surface, then using an oxidant to oxidize the titanium dioxide nanosheets loaded with the metal or metal oxide, and finally washing to remove the loaded product on the surface of the titanium dioxide nanosheets to obtain a same-plane heterojunction
[101] -[oxidized 101] material.
[0006] Preferably, the specific preparation process of the hydrothermal method is as follows: add 30-50 mL of anhydrous ethanol to a beaker, add 10-15 mL of butyl titanate thereto, stir magnetically for 15-30 min, add 3-5 mL of 1-2 M citric acid solution, 2-3 mL of ammonia water, and then ultrasonicate for 20-30 min, transfer the mixed solution to a 100 mL autoclave containing a polytetrafluoroethylene liner, react in an oven at 150-180 ° C for 15-24 h, filter, wash three times with deionized water and ethanol, and then dry in an oven at 60-90 ° C for 6-12 h, and then place in a muffle furnace and calcine at 400-500 ° C for 2-4 h to obtain titanium dioxide nanosheets.
[0007] Preferably, the specific process of loading metal or metal oxide on the surface of titanium dioxide is as follows: weigh 0.5-1g of titanium dioxide nanosheets and place them in a beaker, add 40-50mL of deionized water and 0.1-0.3g of polyethylene glycol 400, ultrasonically disperse for 15-30min, then add 0.01-0.05g of nickel nitrate, and then add 2-3mL of hydrazine hydrate for reduction to precipitate nickel on the surface of titanium dioxide nanosheets.
[0008] Preferably, the specific process of loading metal or metal oxide on the surface of titanium dioxide is as follows: weigh 0.8g of titanium dioxide nanosheets and place them in a beaker, add 45mL of deionized water and 0.2g of polyethylene glycol 400, ultrasonically disperse for 25min, then add 0.03g of nickel nitrate, and then add 2.5mL of hydrazine hydrate for reduction to precipitate nickel on the surface of titanium dioxide nanosheets.
[0009] Preferably, the specific process of loading metal or metal oxide on the surface of titanium dioxide is as follows: using a photocatalytic redox system, weighing 0.5-1g of titanium dioxide nanosheets and placing them in a beaker, adding 40-50mL of deionized water, adding 1-2mL of ethanol or methanol or tert-butanol as a sacrificial agent, ultrasonically dispersing for 15-30min, then adding 0.01-0.05g of nickel nitrate, and irradiating the mixture under a V-Light lamp panel for 30-50min to precipitate metallic nickel on the surface of the titanium dioxide nanosheets.
[0010] Preferably, the specific process of loading metal or metal oxide on the surface of titanium dioxide is as follows: using a photocatalytic redox system, weigh 0.8 g of titanium dioxide nanosheets and place them in a beaker, add 45 mL of deionized water, add 1.5 mL of ethanol or methanol or tert-butanol as a sacrificial agent, ultrasonically disperse for 20 minutes, then add 0.03 g of nickel nitrate, and irradiate the mixture under a V-Light lamp for 40 minutes to precipitate metallic nickel on the surface of the titanium dioxide nanosheets.
[0011] Preferably, the oxidant is a potassium permanganate solution, and the specific operation is: after mixing the titanium dioxide nanosheets with metal precipitated on the surface with the potassium permanganate solution, the titanium dioxide nanosheets are evenly dispersed, stirred and refluxed at 50-150° C. for 12-24 hours, centrifuged after the reaction is completed, washed three times with deionized water and ethanol, and dried at 50-100° C. to obtain a crude product.
[0012] Preferably, 1 M HCl is used to wash and remove the loaded products on the surface of the titanium dioxide nanosheets.
[0013] The advantages and positive effects of the present invention are as follows: the present invention adopts the method of "shielding, oxidation, and deshielding" to prepare a
[101] -[oxidized 101] surface heterojunction. First, TiO2 nanosheets are prepared, and then metal ions are reduced by light deposition, a reducing agent, or metal oxides are deposited by alkali to form a shielding area on the nanosheet. Next, the exposed layer is oxidized by potassium permanganate to form an oxidized
[101] surface, and then the shielding is removed to expose the unmodified
[101] surface, and a
[101] -[oxidized 101] surface heterojunction is successfully prepared on the surface of the TiO2 nanosheet. The successful construction of the same-face heterojunction greatly promotes the separation of electrons and holes, thereby improving the photocatalytic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a schematic diagram of the present invention.
[0015] Figure 2 This is a SEM image of flaky TiO2.
[0016] Figure 3 TEM lattice fringe image of the same-plane heterojunction
[101] -oxidized
[101] titanium dioxide. DETAILED DESCRIPTION
[0017] In order to make the objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below.
[0018] Embodiment 1
[0019] Step 1) Add 45 mL of anhydrous ethanol to a beaker, add 14 mL of butyl titanate thereto, stir magnetically for 15-30 min, add 3-5 mL of 1-2 M citric acid solution, 2-3 mL of ammonia water, and then ultrasonicate for 20-30 min, transfer the mixed solution to a 100 mL autoclave containing a polytetrafluoroethylene liner, react in an oven at 150-180 ° C for 15-24 h, filter, wash three times with deionized water and ethanol, and then dry in an oven at 60-90 ° C for 6-12 h, then place in a muffle furnace and calcine at 400-500 ° C for 2-4 h to obtain titanium dioxide nanosheets.
[0020] Step 2) Weigh 0.9 g of titanium dioxide nanosheets into a beaker, add 48 mL of deionized water and 0.25 g of polyethylene glycol 400, and then ultrasonically disperse for 15-30 min, then add 0.04 g of nickel nitrate, and then add 2.5 mL of hydrazine hydrate for reduction to precipitate nickel on the surface of the titanium dioxide nanosheets.
[0021] Step 3) After the titanium dioxide nanosheets with precipitated metal on the surface are mixed with potassium permanganate solution, they are evenly dispersed, stirred and refluxed at 50-150° C. for 12-24 hours, centrifuged after the reaction is completed, washed three times with deionized water and ethanol, and dried at 50-100° C. to obtain a crude product.
[0022] Step 4) Wash the product in step 3) with 1M hydrochloric acid to remove the nickel loaded on the surface of the titanium dioxide nanosheets, and obtain the same-plane heterojunction
[101] -oxidized
[101] titanium dioxide.
[0023] Embodiment 2
[0024] Step 1) Add 35 mL of anhydrous ethanol to a beaker, add 11 mL of butyl titanate thereto, stir magnetically for 15-30 min, add 3-5 mL of 1-2 M citric acid solution, 2-3 mL of ammonia water, and then ultrasonicate for 20-30 min, transfer the mixed solution to a 100 mL autoclave containing a polytetrafluoroethylene liner, react in an oven at 150-180 ° C for 15-24 h, filter, wash three times with deionized water and ethanol, and then dry in an oven at 60-90 ° C for 6-12 h, then place in a muffle furnace and calcine at 400-500 ° C for 2-4 h to obtain titanium dioxide nanosheets.
[0025] Step 2) Weigh 0.6 g of titanium dioxide nanosheets into a beaker, add 40-50 mL of deionized water and 0.15 g of polyethylene glycol 400, and then ultrasonically disperse for 15-30 min, then add 0.02 g of nickel nitrate, and then add 2.1 mL of hydrazine hydrate for reduction to precipitate nickel on the surface of the titanium dioxide nanosheets.
[0026] Step 3) After the titanium dioxide nanosheets with precipitated metal on the surface are mixed with potassium permanganate solution, they are evenly dispersed, stirred and refluxed at 50-150° C. for 12-24 hours, centrifuged after the reaction is completed, washed three times with deionized water and ethanol, and dried at 50-100° C. to obtain a crude product.
[0027] Step 4) Wash the product in step 3) with 1M hydrochloric acid to remove the nickel loaded on the surface of the titanium dioxide nanosheets, and obtain the same-plane heterojunction
[101] -oxidized
[101] titanium dioxide.
[0028] Embodiment 3
[0029] Step 1) Add 40 mL of anhydrous ethanol to a beaker, add 13 mL of butyl titanate thereto, stir magnetically for 15-30 min, add 3-5 mL of 1-2 M citric acid solution, 2-3 mL of ammonia water, and then ultrasonicate for 20-30 min, transfer the mixed solution to a 100 mL autoclave containing a polytetrafluoroethylene liner, react in an oven at 150-180 ° C for 15-24 h, filter, wash three times with deionized water and ethanol, and then dry in an oven at 60-90 ° C for 6-12 h, then place in a muffle furnace and calcine at 400-500 ° C for 2-4 h to obtain titanium dioxide nanosheets.
[0030] Step 2) Weigh 0.7 g of titanium dioxide nanosheets into a beaker, add 40-50 mL of deionized water and 0.2 g of polyethylene glycol 400, and then ultrasonically disperse for 15-30 min, then add 0.01-0.05 g of nickel nitrate, and then add 2-3 mL of hydrazine hydrate for reduction to precipitate nickel on the surface of the titanium dioxide nanosheets.
[0031] Step 3) After the titanium dioxide nanosheets with precipitated metal on the surface are mixed with potassium permanganate solution, they are evenly dispersed, stirred and refluxed at 50-150° C. for 12-24 hours, centrifuged after the reaction is completed, washed three times with deionized water and ethanol, and dried at 50-100° C. to obtain a crude product.
[0032] Step 4) Wash the product in step 3) with 1M hydrochloric acid to remove the nickel loaded on the surface of the titanium dioxide nanosheets, and obtain the same-plane heterojunction
[101] -oxidized
[101] titanium dioxide.
[0033] Embodiment 4
[0034] Step 1) Add 30-50mL of anhydrous ethanol to a beaker, add 10-15mL of butyl titanate thereto, stir magnetically for 15-30min, add 3-5mL of 1-2M citric acid solution and 2-3mL of ammonia water, then ultrasonicate for 20-30min, transfer the mixed solution to a 100mL autoclave containing a polytetrafluoroethylene liner, react in an oven at 150-180°C for 15-24h, filter, wash three times with deionized water and ethanol, then dry in an oven at 60-90°C for 6-12h, then place in a muffle furnace and calcine at 400-500°C for 2-4h to obtain titanium dioxide nanosheets.
[0035] Step 2) Using a photocatalytic redox system, weigh 0.8 g of titanium dioxide nanosheets and place them in a beaker, add 45 mL of deionized water, add 1.5 mL of ethanol or methanol or tert-butanol as a sacrificial agent, ultrasonically disperse for 20 minutes, then add 0.03 g of nickel nitrate, and irradiate the mixture under a V-Light lamp for 40 minutes to precipitate metallic nickel on the surface of the titanium dioxide nanosheets.
[0036] Step 3) After the titanium dioxide nanosheets with precipitated metal on the surface are mixed with potassium permanganate solution, they are evenly dispersed, stirred and refluxed at 50-150° C. for 12-24 hours, centrifuged after the reaction is completed, washed three times with deionized water and ethanol, and dried at 50-100° C. to obtain a crude product.
[0037] Step 4) washing the product in step 3) with hydrochloric acid to remove the nickel loaded on the surface of the titanium dioxide nanosheets, thereby obtaining the same-plane heterojunction
[101] -oxidized
[101] titanium dioxide.
[0038] Embodiment 5
[0039] Step 1) Add 30-50mL of anhydrous ethanol to a beaker, add 10-15mL of butyl titanate thereto, stir magnetically for 15-30min, add 3-5mL of 1-2M citric acid solution and 2-3mL of ammonia water, then ultrasonicate for 20-30min, transfer the mixed solution to a 100mL autoclave containing a polytetrafluoroethylene liner, react in an oven at 150-180°C for 15-24h, filter, wash three times with deionized water and ethanol, then dry in an oven at 60-90°C for 6-12h, then place in a muffle furnace and calcine at 400-500°C for 2-4h to obtain titanium dioxide nanosheets.
[0040] Step 2) Weigh 0.6 g of titanium dioxide nanosheets and place them in a beaker, add 42 mL of deionized water, add 1.2 mL of ethanol or methanol or tert-butanol as a sacrificial agent, ultrasonically disperse for 15-30 minutes, then add 0.02 g of nickel nitrate, and irradiate the mixture under a V-Light lamp for 30-50 minutes to precipitate metallic nickel on the surface of the titanium dioxide nanosheets.
[0041] Step 3) After the titanium dioxide nanosheets with precipitated metal on the surface are mixed with potassium permanganate solution, they are evenly dispersed, stirred and refluxed at 50-150° C. for 12-24 hours, centrifuged after the reaction is completed, washed three times with deionized water and ethanol, and dried at 50-100° C. to obtain a crude product.
[0042] Step 4) Wash the product in step 3) with 1M hydrochloric acid to remove the nickel loaded on the surface of the titanium dioxide nanosheets, and obtain the same-plane heterojunction
[101] -oxidized
[101] titanium dioxide.
[0043] In the above five embodiments, potassium permanganate is used to oxidize the silicon dioxide nanosheets loaded with metal or metal oxide, but the oxidant is not limited to potassium permanganate, and other oxidants such as hydrogen peroxide can also be used to oxidize silicon dioxide. Several different preparation methods are introduced above through five different embodiments. The advantages of the same-plane heterojunction
[101] -oxidized
[101] titanium dioxide of the present invention are verified by experiments below.
[0044] Table 1: Degradation data of acid chrome blue K
[0045]
[0046] Table Notes: A0 = 0.622, degradation rate = (A0-At) / A0
[0047] Table 2: Degradation data of methyl orange
[0048]
[0049] Notes: A0 = 0.726, degradation rate = (A0-At) / A0
[0050] From the simulated wastewater degradation experiment (degradation of methyl orange solution and acid chrome blue K solution), it can be concluded that under the irradiation of V-Light simulated sunlight LED lamp, the same-plane heterojunction
[101] -oxidized
[101] titanium dioxide has the best degradation effect on acid chrome blue K solution and methyl orange solution. This proves that the same-plane heterojunction
[101] -oxidized
[101] titanium dioxide of the present invention can greatly improve the photocatalytic efficiency.
[0051] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A method for preparing a two-dimensional on-plane heterojunction material, characterized in that: First, titanium dioxide nanosheets are prepared by a hydrothermal method, and then a protective metal or metal oxide is loaded on the surface of the titanium dioxide nanosheets. Then, an oxidant is used to oxidize the titanium dioxide nanosheets loaded with the metal or metal oxide, and finally, the loaded products on the surface of the titanium dioxide nanosheets are washed away to obtain a same-plane heterojunction [101]-[oxidized 101] material.
2. The method for preparing a two-dimensional in-plane heterojunction material according to claim 1, characterized in that: The specific preparation process of the hydrothermal method is as follows: add 30-50 mL of anhydrous ethanol into a beaker, add 10-15 mL of butyl titanate thereto, stir magnetically for 15-30 min, add 3-5 mL of 1-2 M citric acid solution and 2-3 mL of ammonia water, then ultrasonicate for 20-30 min, transfer the mixed solution to a 100 mL autoclave containing a polytetrafluoroethylene liner, react in an oven at 150-180° C. for 15-24 h, filter, wash three times with deionized water and ethanol, and then dry in an oven at 60-90° C. for 6-12 h, then place in a muffle furnace and calcine at 400-500° C. for 2-4 h to obtain titanium dioxide nanosheets.
3. The method for preparing a two-dimensional in-plane heterojunction material according to claim 1, characterized in that: The specific process of loading metal or metal oxide on the surface of titanium dioxide is as follows: weigh 0.5-1g of titanium dioxide nanosheets and place them in a beaker, add 40-50mL of deionized water and 0.1-0.3g of polyethylene glycol 400, ultrasonically disperse for 15-30min, then add 0.01-0.05g of nickel nitrate, and then add 2-3mL of hydrazine hydrate for reduction to precipitate nickel on the surface of titanium dioxide nanosheets.
4. The method for preparing a two-dimensional in-plane heterojunction material according to claim 3, characterized in that: The specific process of loading metal or metal oxide on the surface of titanium dioxide is as follows: weigh 0.8g of titanium dioxide nanosheets and place them in a beaker, add 45mL of deionized water and 0.2g of polyethylene glycol 400, ultrasonically disperse for 25min, then add 0.03g of nickel nitrate, and then add 2.5mL of hydrazine hydrate for reduction to precipitate nickel on the surface of titanium dioxide nanosheets.
5. The method for preparing a two-dimensional in-plane heterojunction material according to claim 1, characterized in that: The specific process of loading metal or metal oxide on the surface of titanium dioxide is as follows: using a photocatalytic redox system, weigh 0.5-1g of titanium dioxide nanosheets and place them in a beaker, add 40-50mL of deionized water, add 1-2mL of ethanol or methanol or tert-butanol as a sacrificial agent, ultrasonically disperse for 15-30 minutes, then add 0.01-0.05g of nickel nitrate, place the mixture under a V-Light lamp panel and irradiate for 30-50 minutes to precipitate metallic nickel on the surface of the titanium dioxide nanosheets.
6. The method for preparing a two-dimensional in-plane heterojunction material according to claim 5, characterized in that: The specific process of loading metal or metal oxide on the surface of titanium dioxide is as follows: using a photocatalytic redox system, weigh 0.8 g of titanium dioxide nanosheets and place them in a beaker, add 45 mL of deionized water, add 1.5 mL of ethanol or methanol or tert-butanol as a sacrificial agent, ultrasonically disperse for 20 minutes, then add 0.03 g of nickel nitrate, place the mixture under a V-Light lamp panel and irradiate for 40 minutes to precipitate metallic nickel on the surface of the titanium dioxide nanosheets.
7. The method for preparing a two-dimensional in-plane heterojunction material according to claim 1, characterized in that: The oxidant is a potassium permanganate solution, and the specific operation is: after mixing the titanium dioxide nanosheets with metal precipitated on the surface with the potassium permanganate solution, the titanium dioxide nanosheets are evenly dispersed, stirred and refluxed at 50-150° C. for 12-24 hours, centrifuged after the reaction is completed, washed three times with deionized water and ethanol, and dried at 50-100° C. to obtain a crude product.
8. The method for preparing a two-dimensional in-plane heterojunction material according to claim 1, characterized in that: 1 M HCl was used to wash away the loaded products on the surface of the titanium dioxide nanosheets.
Citation Information
Patent Citations
MIXED CRYSTAL TiO2 / BiOBr COMPOSITE AND PREPARATION METHOD AND APPLICATION THEREOF
AU2020102258A4
PREPARATION METHOD AND APPLICATION OF g-C3N4 / (101)-(001)-TiO2 COMPOSITE MATERIAL
AU2020102640A4